Wpływ teologii Ksiąg Kronik na Pierwszą Księgę Machabejską na przykładzie 2Krn 25,1-28 i 1Mch 11 - Nawrot, Janusz (Collectanea Theologica, 2020)
The Old Testament includes many texts written by hagiographers that are later on taken up in a new or wider historical-theological context. In his work, the author of the First Book of Maccabees used earlier texts from the inspired books. He did not, however, quote them explicitly, but utilized chosen terminological borrowings. The material of the Books of Chronicles is part of the hagiographer’s wider project of borrowing the theology of almost all the protocanonical books in order to strengthen his narration. He used descriptions of events, people and their behaviour which were a point of reference with regards to the evaluation of the action of particular characters during the time of the Maccabean Revolt. On the one hand, the theology of the previous biblical books lays the foundations for writing one’s own original work. On the other hand, this work sheds meaningful light on the theological potential of the previous texts and thus opens them for the future.